ANALYSIS OF THE SLANG WORD 'KUY' IN EVERYDAY LANGUAGE CONTEXT - Suci Rahmadani; Jamaluddin Nasution; Widya Karolina Br Pardede; Alyah Putri Nabilla; Kesya Klarissya Br Pandia (Smart Education, 2025)
Abstract: This study analyzes the use of the slang word â€œkuyâ€ in the daily language of Indonesian society, particularly among teenagers and young adults. Using a qualitative approach and descriptive-analytical method, data were collected through questionnaires from 107 respondents, in-depth interviews, social media observation, and digital documentation. The findings show that â€œkuyâ€ originates from the phonological reversal of the word â€œyukâ€ in prokem language, which emerged in the 1980s and gained popularity on social media around 2014. Semantically, 89.7% of respondents understand â€œkuyâ€ as an invitation, but pragmatically, it also serves as a symbol of social closeness and group identity, with 57.9% considering it important to express familiarity among peers. The word is most commonly used to invite someone to do something (52.8%) and appears more frequently in social media communication than in face-to-face interaction. Its usage is moderate, with 85% of respondents using it occasionally, reflecting the younger generationâ€™s ability to code-switch according to the communication context. This study concludes that â€œkuyâ€ is not only a linguistic expression but also a cultural artifact that reflects the creativity and social dynamics of Indonesiaâ€™s urban digital generation.Â Keywords: slang, kuy, sociolinguistics, prokem language, social media, adolescent identity, language variation, digital communication, Gen Z, Indonesian slang.Â Abstrak: Studi ini menganalisis penggunaan kata slang